2019
DOI: 10.18632/aging.102062
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of serum lactate kinetics in critically ill patients with cirrhosis and acute-on-chronic liver failure: a multicenter study

Abstract: Lactate clearance (Δ24Lac) was reported to be inversely associated with mortality in critically ill patients. The aim of our study was to assess the value of Δ24Lac for the prognosis of critically ill patients with cirrhosis and acute-on-chronic liver failure (ACLF). We analysed 954 cirrhotic patients with hyperlactatemia admitted to intensive care units (ICUs) in the United States and eastern China. The patients were followed up for at least 1 year. In the unadjusted model, we observed a 15% decrease in hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
1
18
0
1
Order By: Relevance
“…Non Two Chinese groups have externally validated the LiFe score. 3,17 Yao et al 3 used the US single-centre database Medical Information Mart for Intensive Care-III (MIMIC-III) 22 for analysis. The cohort had a similar mean age (57.2 (SD 11.8)) and an ICU mortality of 31.5%.…”
Section: One-year Survivorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non Two Chinese groups have externally validated the LiFe score. 3,17 Yao et al 3 used the US single-centre database Medical Information Mart for Intensive Care-III (MIMIC-III) 22 for analysis. The cohort had a similar mean age (57.2 (SD 11.8)) and an ICU mortality of 31.5%.…”
Section: One-year Survivorsmentioning
confidence: 99%
“…Of note, this group reported that replacing lactate with lactate clearance (reduction within the first 24 h) significantly improved discrimination (in-hospital mortality AUC 0.75; 90-day: 0.70 and one-year: 0.69, all P < 0.01 for comparisons). 17 A small single centre study from Scotland (n ¼ 83) proposed a similar score to LiFe which also incorporated albumin and found a good discrimination to predict one-year survival. 24 This study also showed that patients with variceal bleeding had a lower mortality, as reported in previous studies.…”
Section: One-year Survivorsmentioning
confidence: 99%
“…The level of lactate in serum has become an important objective indicator to evaluate the prognosis of patients with cirrhosis and LF [41][42][43]. In addition, it has been shown that the rate of lactate clearance is a good and independent predictor of death in critically ill patients with cirrhosis and acute-on-chronic liver failure [44]. Creatinine is a metabolite that is a byproduct of muscle metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring of lactate levels is important in ICU patients with sepsis [ 23 , 24 ]. The liver accounts for 70% of lactate clearance in the human body [ 25 ], and several studies have focused on the importance of lactate and lactate clearance in critically ill patients with cirrhosis and in ACLF patients [ 7 , 8 , 26 , 27 ]. Some studies proved that using lactate level could improve the accuracy of the traditional model, and constructed improved models like CLIF-C ACLFs Lact [ 8 ] and MELD-LA [ 9 ].…”
Section: Discussionmentioning
confidence: 99%